2016
DOI: 10.1016/j.ejmp.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

NTCP modeling analysis of acute hematologic toxicity in whole pelvic radiation therapy for gynecologic malignancies – A dosimetric comparison of IMRT and spot-scanning proton therapy (SSPT)

Abstract: The SSPT achieves significant reductions in the dose to BM without compromising target coverage, compared with IMRT. The NTCP value for HT3+ in SSPT was significantly lower than in IMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The total scores are assigned 100 points, with the specific allocation is as follows: S T metrics [1][2][3][4] with total points of 24 are used to calculate the points of CTV dose coverage [V46.8Gy (%), V50 Gy (%)], conformity number (CN) and homogeneity index (HI). The rest 76 points are S O metrics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] are assigned to specific dosevolume parameters of five OARs, where rectum, bowel, bladder, sigmoid and femoral heads shared 23, 22, 15, 9 and 7 points, respectively. The details of score points are shown in Table 2.…”
Section: Quick Plan Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The total scores are assigned 100 points, with the specific allocation is as follows: S T metrics [1][2][3][4] with total points of 24 are used to calculate the points of CTV dose coverage [V46.8Gy (%), V50 Gy (%)], conformity number (CN) and homogeneity index (HI). The rest 76 points are S O metrics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] are assigned to specific dosevolume parameters of five OARs, where rectum, bowel, bladder, sigmoid and femoral heads shared 23, 22, 15, 9 and 7 points, respectively. The details of score points are shown in Table 2.…”
Section: Quick Plan Reviewmentioning
confidence: 99%
“…As an advanced modality of radiotherapy for intensity modulated radiation therapy (IMRT) combined with an image guiding system, helical tomotherapy (HT) has been proven to be efficient for cervical cancer [2]. Due to the unique physical characteristic of Bragg peakand intensity modulated proton therapy (IMPT) would offer the best sparing healthy tissue as compared with IMRT, volumetric modulated arc therapy (VMAT), and HT, while maintaining excellent target coverage or conformity [3][4][5]. HT and IMPT share standard uncertainties in treatment delivery, including target definition, target motion, normal tissue motion, and patient setup uncertainties, which sets the margin from the clinical target volume (CTV) to planning target volume (PTV) based on clinical experience in the process of the radiotherapy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dosimetric studies have shown a potential sparing of bone marrow by spot-scanning PBT [ 22 , 23 ]. In previous work we conducted an in silico study in 13 postoperative gynecologic malignancy patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment plan, the dose was prescribed to the clinical target volume (CTV). In our facility, the beam‐specific optimization margins for the CTV are specified . A treatment plan was prepared for each patient, and if necessary, a replan or boost plan was devised.…”
Section: Methodsmentioning
confidence: 99%
“…In our facility, the beam-specific optimization margins for the CTV are specified. 21,22 A treatment plan was prepared for each patient, and if necessary, a replan or boost plan was devised. The number of treatment plans for each category is listed in Table 2.…”
Section: C | Treatment Planningmentioning
confidence: 99%